2019
DOI: 10.3390/nu11030506
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Activates Osteoblastogenesis and Inhibits Osteoclastogenesis via Wnt/β-Catenin/ATF4 Signaling Pathways

Abstract: This study evaluated the effects of vitamin C on osteogenic differentiation and osteoclast formation, and the effects of vitamin C concentration on bone microstructure in ovariectomized (OVX) Wistar rats. Micro-computed tomography analysis revealed the recovery of bone mineral density and bone separation in OVX rats treated with vitamin C. Histomorphometrical analysis revealed improvements in the number of osteoblasts, osteoclasts, and osteocytes; the osteoblast and osteoclast surface per bone surface; and bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 67 publications
4
41
1
Order By: Relevance
“…Prior work has confirmed the importance of vitamin C in maintaining bone health by demonstrating a positive association with vitamin C intake and BMD at the femoral neck and lumbar spine along with a 33% lower risk of osteoporosis [ 24 ]. These effects may stem from the suppression of osteoclast activity and the differentiation of osteoblasts by vitamin C [ 25 , 26 ]. In this regard, the association between vitamin C metabolism and P1NP levels may reflect the well-established osteogenic effects of vitamin C on osteoblast differentiation and matrix deposition [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has confirmed the importance of vitamin C in maintaining bone health by demonstrating a positive association with vitamin C intake and BMD at the femoral neck and lumbar spine along with a 33% lower risk of osteoporosis [ 24 ]. These effects may stem from the suppression of osteoclast activity and the differentiation of osteoblasts by vitamin C [ 25 , 26 ]. In this regard, the association between vitamin C metabolism and P1NP levels may reflect the well-established osteogenic effects of vitamin C on osteoblast differentiation and matrix deposition [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…VC deficiency was also linked to increased expression of tumour necrosis factor ligand superfamily member 11 (RANKL), which acts as a critical osteoclast and bone resorption inducer, but also an inflammatory mediator [29]. A recent study has demonstrated that ostoblastogenesis and osteoclastogenesis in osteoporosis rat models are in fact regulated by a shared serine/threonine kinase and mitogen-activated protein kinase (MAPK) signalling pathway, which is fine-tuned by vitamin C [35].…”
Section: Studies On Animal Modelsmentioning
confidence: 99%
“…Enhances osteoblastogenesis and inhibits osteoclastogenesis via Wnt/β-catenin signaling [22]. Vitamin C contributes to normal function of bones and teeth (EFSA opinion).…”
Section: Vitamin C (Ascorbic Acid)mentioning
confidence: 99%